TECHNIQUE AND IDEOLOGY OF VOCATIVES AND PROPER NAMES IN THE HOBBIT - Ratnasari, Weni; Yuliasri, Issy; Hartono, Rudi (Language Circle: Journal of Language and Literature, 2016)
The aim of this present study is to reveal the technique and ideology of vocatives and proper names in The Hobbit. To be more precise, this study also examine translation quality of vocatives and proper names by assessing its accuracy, readability and acceptability. This study applied descriptive qualitative research. Aside from getting data from The Hobbit, the data are gotten from target readersâ and expert ratersâ questionnaire. Based on the analysis, the translator applied 9 techniques in translating 75 vocatives. In dealing with proper names, the translator used 7 translation techniques. This study reveals that the translator adopted more foreignization ideology in rendering vocatives and proper names into Indonesian. It can be concluded that the translator intend to keep the originality of this novel, since he mostly copied the name of characters and georagphical name that appeared in this novel. Dealing with the quality of translation, it is proved that there are various translation quality of vocatives and proper names found in The Hobbit. It covers accurate, less accurate, inaccurate, acceptable, less acceptable, inacceptable, high readability, sufficient readability and low readability translation.Â